2007
DOI: 10.1088/0031-9155/52/20/012
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cerebral endothelial cell morphology by extracellular calcium

Abstract: Cerebral endothelial cells interconnected by tight and adherens junctions constitute the structural basis of the blood-brain barrier. Extracellular calcium ions have been reported to play an important role in the formation and maintenance of the junctional complex. However, little is known about the action of calcium depletion on the structural characteristics of cerebral endothelial cells. Using atomic force microscopy we analyzed the effect of calcium depletion and readdition on the shape and size of living … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 32 publications
(38 reference statements)
1
32
0
Order By: Relevance
“…These results indicate that the chitosan-chitosan and gelatin-gelatin fibers interacted and bonded during the cross-linking process. Previous reports described a phenomenon in which the fibers were curled and conglutinated with each other after cross-linking [26,30]. The inset images show the morphology of the ABV scaffold before and after cross-linking at the failure section.…”
Section: Tensile Strength and Burst Strengthmentioning
confidence: 95%
“…These results indicate that the chitosan-chitosan and gelatin-gelatin fibers interacted and bonded during the cross-linking process. Previous reports described a phenomenon in which the fibers were curled and conglutinated with each other after cross-linking [26,30]. The inset images show the morphology of the ABV scaffold before and after cross-linking at the failure section.…”
Section: Tensile Strength and Burst Strengthmentioning
confidence: 95%
“…These proteins can be divided into four families: the immunoglobulin-like adhesion molecules, integrins, cadherins and selectins (Buckley et al 1998). Except the first, all are calcium dependent, hence extracellular calcium plays key role in cell-cell adhesion (Wilhelm et al 2007). …”
Section: Role Of Plasma Membranementioning
confidence: 99%
“…CECs are very sensitive to environmental changes (Wilhelm et al 2008;Wilhelm et al 2007), therefore in some pathological cases their mechanical modulation can reversibly open the BBB (Bálint et al 2007a). Circulating factors within the blood can alter their mechanical properties (Lee et al 2011).…”
Section: Insight Intomentioning
confidence: 99%
See 1 more Smart Citation
“…Brain endothelial tight junction proteins, which were shown to be involved in the transmigration of melanoma cells, are linked to the actin cytoskeleton and are influenced by ROCKs. Inhibition of Rho/ROCK signaling has been shown to prevent Ca 2+ -induced junctional disassembly in both epithelial and brain endothelial cells (Samarin et al 2007, Wilhelm et al 2007). ROCK enhances BBB permeability via disruption of tight junction proteins in subarachnoid hemorrhage (Fujii et al 2012), while inhibition of ROCK was found to attenuate the HIV-1 Tat protein-induced decrease in occludin levels in brain endothelial cells (Xu et al 2012).…”
mentioning
confidence: 99%